2003
DOI: 10.1186/1475-2875-2-43
|View full text |Cite
|
Sign up to set email alerts
|

Improving ability to identify malaria and correctly use chloroquine in children at household level in Nakonde District, Northern Province of Zambia

Abstract: Background: This study investigated causes of malaria and how cases were managed at household level, in order to improve the ability to identify malaria and ensure correct use of chloroquine. It was conducted in Nakonde District, Northern Province of Zambia, between 2000 and 2001. Nakonde district is in a hyperendemic malaria province, where Plasmodium falciparum is predominant. The district has a total population of 153, 548 people, the majority of whom are peasant farmers. The main aim of the post interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…17,36 Kaona and Tuba found that training motivators and vendors were contributing to compliance with standard therapeutic doses and correct identification of malaria. 11 Another study showed that community health education can help improve health seeking behaviour. 37 Additionally, other studies revealed that illiteracy with regards to health education 31 is an important factor to guiding behaviour change messages, 32,33,38 and [Mwanje, personal communication, 2013] as well as taking socioeconomic and sociocultural aspects of particular communities into consideration in developing tailor-made interventions to avoid disrupting economic and cultural activities, and hence succeed with community commitment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,36 Kaona and Tuba found that training motivators and vendors were contributing to compliance with standard therapeutic doses and correct identification of malaria. 11 Another study showed that community health education can help improve health seeking behaviour. 37 Additionally, other studies revealed that illiteracy with regards to health education 31 is an important factor to guiding behaviour change messages, 32,33,38 and [Mwanje, personal communication, 2013] as well as taking socioeconomic and sociocultural aspects of particular communities into consideration in developing tailor-made interventions to avoid disrupting economic and cultural activities, and hence succeed with community commitment.…”
Section: Discussionmentioning
confidence: 99%
“…6 Knowledge studies have been conducted in Zambia from as far back as the late 1990s, 7,8 and contribute to the understanding of community determinants of malaria; although, as in Swaziland, 9 it is only recently that the importance of these studies has been recognised for use in control efforts in Zambia. 10,11 The nation has also made strides in reaching the global World Health Organisation (WHO) targets in control, 12 including long-lasting insecticide-treated net (ITN) distribution, high indoor residual spray (IRS) coverage and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Although malaria medicines dispensed within public health facilities and consultancy were free for all in rural areas, the frequent experience of receiving a prescription instead of medicines probably contributed to the widespread self-medication practices reported by participants. Self-medication has been found to contribute to impromptu and ineffective treatment of malaria infections [ 31 ]. Studies from several African countries have also found inequitable ownership and utilization of ITNs as indicated by participants in this study [ 32 - 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interventions reviewed included optimizing case-management and services in health facilities [ 4 - 8 ] or improving dispensing practices of drug shop attendants and private practitioners [ 9 - 14 ] as well as community based approaches [ 15 - 17 ]. Two general approaches to improving user malaria treatment practices have been pursued: 1) health education campaigns; [ 18 , 19 ] and 2) interventions that specifically provide information on how to take anti-malarials [ 20 ], including pre-packaging and pictorial and verbal instructions [ 21 - 23 ]. The main finding from the review is that most interventions so far have been conducted on a rather small scale and that few have been appropriately evaluated.…”
Section: Introductionmentioning
confidence: 99%